The Role Of Brand Image On Purchasing Decisions With Influencer Marketing And Online Customer Reviews As Mediation Variables - Megawati, Megawati; Komariyatin, Nurul (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2024)
Apparel represents a significant element of public life, with numerous individuals recognizing it as an opportunity for commercial endeavors. The advancement of technology has instigated various transformations, particularly within the marketing sector, where the emergence of internet technology has facilitated online sales campaigns for clothing. A pertinent example of this phenomenon is the Lovable Hijab Brand, situated in Bangsri, Jepara, Central Java. A widely utilized marketing strategy encompasses the application of influencer marketing to enhance the brand image of a company or product, thereby assisting target consumers in their purchasing decisions. This study aims to explore the role of brand image in the purchasing decisions influenced by marketing and online customer reviews, which act as mediating variables. A quantitative approach has been adopted, employing probability sampling techniques. The population for this research consists of residents from Bangsri who have made purchases at Lovable Hijab. The total number of respondents in this study is 138. Data collection is executed through the distribution of questionnaires, with analysis conducted utilizing the Partial Least Squares (PLS) method. The research findings reveal a significant influence of brand image on purchase decisions, an impact of brand image on influencer marketing, an effect of brand image in relation to online customer reviews, and a notable interrelation between influencer marketing and online customer reviews affecting purchasing decisions.